Numerical investigation of the effect of temperature on the formability of a thermoplastic fibre metal laminate - Sivakumar, Dhar Malingam (The University of Adelaide, 2012)
Numerical analysis of the stamp forming of FML systems would provide a powerful tool for the optimisation of the process parameters and a fundamental understanding of the deformation behaviour of this material system. This study uses the finite element analysis software, LS-DYNA, to simulate the effect of temperature on the stamp forming of a FML based on a polypropylene based composite. This numerical model is validated through comparison with experiments conducted using a hemispherical punch and non-contact optical measurement system. The combination of real-time optical strain measurement and non-linear FEA to analyse and predict the forming of this material is a significant advancement in the understanding of FML systems. A major conclusion derived from the FE simulations and experiments is that temperature is an important metric to the forming behaviour of the FML.